2013
DOI: 10.1177/0333102413487445
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic dopaminergic stimulation in cluster headache

Abstract: Our data suggest that cluster headache is associated with an impaired dopaminergic stimulation. This finding supports the body of evidence that cluster headache is associated with a functional abnormality of the hypothalamus and that this association is a primary (i.e. idiopathic) and not a secondary phenomenon during the bout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…First, KD can induce an increase in brain dopaminergic activity, as measured in the meso-cortical dopaminergic system of mice ( 6 ). This datum is relevant to our study because it is known that CH is associated with impaired dopaminergic stimulation ( 7 ). Nonetheless, in a previous report about a drug-resistant chronic patient, we observed that treatment with a dopaminergic agonist improved CH and reverted his trigeminal neurophysiological abnormalities ( 8 ), typical of the active phase of cluster ( 9 ).…”
Section: Discussionmentioning
confidence: 98%
“…First, KD can induce an increase in brain dopaminergic activity, as measured in the meso-cortical dopaminergic system of mice ( 6 ). This datum is relevant to our study because it is known that CH is associated with impaired dopaminergic stimulation ( 7 ). Nonetheless, in a previous report about a drug-resistant chronic patient, we observed that treatment with a dopaminergic agonist improved CH and reverted his trigeminal neurophysiological abnormalities ( 8 ), typical of the active phase of cluster ( 9 ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, rotigotine is generally well tolerated even if the duration of treatment lasts up to 6 years, without serious adverse side-effects (the most common of which are somnolence, falls, peripheral oedema, nausea and reactions at the application site). 12,13 So far, a possible relationship between CH and the dopaminergic system is under scrutiny, although CH is associated with impaired dopaminergic stimulation, 14 whereas dopamine inhibits the nociception in the trigeminovascular transmission in animals. 15 Moreover, it is known that the dopaminergic system is strictly involved with pain modulation 16 and its chronification.…”
Section: Discussionmentioning
confidence: 99%
“…VIP and AVP are peptides found in a large proportion of SCN neurons: VIP‐positive neurons are primarily found in the core area of the SCN, and AVP‐positive neurons are found in the shell area . Preliminary studies also suggest cluster headache‐associated changes in other molecules indirectly modulated by the SCN, including PACAP, orexin, orexin receptors, testosterone, prolactin and growth hormone …”
Section: Circadian Rhythms In Painmentioning
confidence: 99%
“…20 Preliminary studies also suggest cluster headache-associated changes in other molecules indirectly modulated by the SCN, including PACAP, orexin, orexin receptors, testosterone, prolactin and growth hormone. [76][77][78][79][80][81][82] Although earlier attempts did not identify a molecular association of clock genes with cluster headache, [83][84][85] more recent studies elucidated changes in circadian transcriptiontranslation feedback loops. In an association study of large Swedish cohorts, a single-nucleotide polymorphism (SNP: rs12649507) in the Clock gene was found to be significantly associated with cluster headache.…”
Section: Cluster Headachementioning
confidence: 99%